Identification of Representation Ability in the Topic of Space Analytical Geometry for Student in Higher Education - Pemu, Nasrullah; Sappaile, Baso Intang; Talib, Ahmad (Mathematics Dept, Math. and Science Faculty, Universitas Negeri Semarang, 2023)
This study aims to identify the representation ability of prospective mathematics teacher students by exploring the material of Space Analytical Geometry. The type of research is design research involving 38 students of the Mathematics Department, FMIPA UNM. The research instruments used are Lesson Plan and e-Task. The e-Task is the instrument combining the LMS Syam-OK and Gdrive for collecting the outputs of these activities. From the results provide an important note that 1) the methods and materials of student representation depend on the knowledge they have, the wider the knowledge they have the various presentation information provided. 2) The method and material of representation shown by students will be more developed if the questions given are challenging. 3) From some of the problems given, the analytical method will be used if the problem requires pictures to be shown in its solution.Penelitian ini bertujuan untuk mengetahui kemampuan representasi mahasiswa calon guru matematika dengan mendalami materi Geometri Analitik Ruang. Jenis penelitian yang digunakan adalah design research yang melibatkan 38 mahasiswa Jurusan Matematika FMIPA UNM. Instrumen penelitian yang digunakan adalah Lesson Plan dan e-Task. E-Task adalah instrumen yang menggabungkan LMS Syam-OK dan Gdrive untuk mengumpulkan output dari kegiatan ini. Dari hasil memberikan catatan penting bahwa 1) metode dan materi representasi siswa bergantung pada pengetahuan yang dimilikinya, semakin luas pengetahuan yang dimilikinya maka berbagai informasi presentasi yang diberikan. 2) Metode dan materi representasi yang ditunjukkan siswa akan lebih berkembang jika soal yang diberikan menantang. 3) Dari beberapa masalah yang diberikan, metode analitik akan digunakan jika masalah tersebut membutuhkan gambar untuk ditampilkan dalam penyelesaiannya.